2020
DOI: 10.32598/ppj.25.1.40
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin enhances the antitumor activity of tamoxifen in B16f10 mouse melanoma cell lines

Abstract: Introduction: Tamoxifen has been used in the treatment of metastatic malignant melanoma more common with other agents in the combined therapy. Up-regulated activity of the mevalonate pathway has been shown in a range of different cancers. Atorvastatin is the most commonly used statin approved for cholesterol reduction by inhibiting the mevalonate pathway and has been shown to inhibit tumor growth. In the present study, we used atorvastatin and tamoxifen combination therapy on B16f10 mouse melanoma cell lines t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…[ 3 8 9 ] Also, there are studies that show statin can enhance the therapeutic efficacy of anticancer drugs in melanoma, indicating its promising role in combination therapy. [ 10 11 ] Nevertheless, previous studies have yielded inconsistent findings. While some large-scale cardiovascular trials have indicated a reduction in melanoma incidence associated with statin use, this effect has not been consistently observed in other studies or meta-analyses examining different types of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…[ 3 8 9 ] Also, there are studies that show statin can enhance the therapeutic efficacy of anticancer drugs in melanoma, indicating its promising role in combination therapy. [ 10 11 ] Nevertheless, previous studies have yielded inconsistent findings. While some large-scale cardiovascular trials have indicated a reduction in melanoma incidence associated with statin use, this effect has not been consistently observed in other studies or meta-analyses examining different types of cancer.…”
Section: Introductionmentioning
confidence: 99%